Progress and future opportunities in the development of vaccines against atherosclerosis - Dania O. Govea-Alonso; Josué Beltrán-López; Jorge A. Salazar-González; Juan Vargas-Morales; Sergio Rosales-Mendoza (Taylor & Francis Group, 2017)
Introduction: Atherosclerosis represents a serious global health problem that demands new therapeutic and prophylactic interventions. Considering that atherosclerosis has autoimmune and inflammatory components, immunotherapy is a possible focus to treat this disease. Areas covered: Based on the analysis of the current biomedical literature, this review describes the status on the development of vaccines against atherosclerosis. Several targets have been identified including sequences of apolipoprotein B100 (ApoB100), cholesteryl ester transfer protein (CETP), heat shock proteins (HSP), extracellular matrix proteins, T cell receptor β chain variable region 31 (TRBV31), the major outer membrane protein (MOMP), and the outer membrane protein 5 (Pomp5) from Chlamydia pneumoniae. Humoral and cellular immunities to these targets have been associated with therapeutic effects in murine models and humans. The evaluation of some candidates in clinical trials is ongoing. Expert commentary: New research paths based on the use of next generation vaccine production platforms are envisioned.